TESTING OF AN AUTONOMOUS MOBILE PHOTOTHERMAL WATER LIFTING INSTALLATION UNDER NATURAL CONDITIONS - Tursunov, Мukhamad; Sabirov, Khabibullo; Eshmatov, Mansur; Xolov, Uygʻun (Innovatsion texnologiyalar, 2024)
This article presents the results of testing in natural environmental conditions of a new mobile device based on a reflective photocell battery equipped with a self-cooling system without additional energy recovery at the cooling period, designed for use in the extraction of water from wells and energy supply to household consumers in villages located in remote areas of the republic with a hot and dry climate. The device was tested in two different modes, photoelectric and photocell modes. The idle voltages were 20.5 V and 25 V in photovoltaic and photothermal modes, respectively, and the short circuit currents were 35.4 A and 44.6 A, respectively. The output power of the device showed values of 516 W and 870 W, respectively. With the help of the apparatus a water pump with a power of 350 W pumped water to a height of 15 m for 5 hours, and an acid battery with a capacity of 200 A-hour was being kept fully charged. During this time 30 m3 of water was pumped out, and the efficiency of the subsystem was 71,4%.